ABRAHAM CAHAN'IN DAVID LEVINSKY ADLI ROMANINA YENİ TARİHSELCİ BİR ÇALIŞMA - Kalay, Faruk (My University, 2015)
Abrahan Cahan 1900'lü yıllarda yaşamış Yahudi Amerikan bir yazardır. The Rise of David Levinsky adlı roman kahramanıyla aynı adı taşıyan kendi yazarı gibi 1865'te Rusya'nın kuzeybatısındaki Kovno adlı bir kasabasında doğan bir genci ele alan otobiyografik özelliklere sahip bir eserdir. Ancak romanın içeriği itibariyle künstleroman ve/veya bildungsroman özellikleri de taşımaktadır. Fakir, genç bir yetim olan Levinsky 1881'de goyim [Yahudilerin kendilerinden olmayanlara verdikleri isim] saldırılarında hayatını kaybettikten sonra Amerika'ya göç etmeye karar verir. Amerika'yı "dünyanın geri kalanı gibi olmayan eşsiz bir ülke" (Cahan, 87) olarak görür. Bu bağlamda Amerika algısı pogromlara maruz kalmış doğu Avrupa Yahudilerinden farksız değildir. "1880-1915 yılları arasında Birleşik Devletlere gelen doğu Avrupa Yahudilerinin ezici bir çoğunluğun fikri Amerikan-Yahudi yaşamının popüler düşüncesinde merkezi bir pozisyonda kendini tutan Ortodoks'lardı" (Singer, 696). Hayatı, Amerika'ya bakış açısı, pogromlardan kaçan Yahudi göçmenlerle aynı olduğunu tekrar söyleyebiliriz. gerçekleştirmesidir. Romanın sonuna doğru kendi sektöründe iş yapan ilk üç arasına girmiştir. Ancak, Amerika'da iş ve kişisel yaşamı ne kadar ilerlemiş olursa olsun, her doğu Avrupalı Yahudi gibi kendini yalnız hissedecektir. Levinsky'nin hayatı, sadece kendi döneminde yaşayan bir göçmenin hayatından ziyade, günümüzde herhangi bir göçmenin maruz kaldığı psikolojik, sosyolojik ve politik sorunları da gözler önüne sermektedir. İşte bu bağlamda The Rise of David Levinsky yeni tarihselci bir bakış açısıyla irdelenecektir

Abraham Cahan is a Jewish American author living in 1900s. His famous novel titled The Rise of David Levinsky has autobiographical characteristics whose protagonist is David Levinsky himself who was born in Kovno, a northwestern Russia, in 1865 like his author. Levinsky, a poor young orphan decides to move America after losing his mother in 1881 Gentile riot. He regards America as “a unique country, unlike the rest of the world” (Cahan, 87). In this sense his perception resembles the other East European Jews who would be exposed to Pogroms. “The notion that the overwhelming majority of east European Jews who came to the United States between 1880 and 1915 were Orthodox has assumed a central position in the popular mythology of American-Jewish life” (Singer, 696). His life, and perspective to America is the same as other Jewish immigrants who flee from the pogroms. In America no matter how he well advance in both business and personal life, he feels estranged to his background like every East-European Jewish. Also Cahan deals with social and sociocultural life of immigrants living in New York. It has In this study, The Rise of David Levinsky will be studied in terms of new historicist criticism Abraham Cahan dealing with immigration and alienation is one of the most important writers in American Jewish history. His first autobiographic novel The Rise of David Levinsky is about a young man having the same name David Levinskywho migrates to America at the beginning of twentieth century. The protagonist who has nothing when he steps onto America earns millions of dollars. The novel is prominent for two reasons: the indication of Jews’ situation and the living conditions in both the US and Russia. In this respect, the novel can be regarded as “the first full-fledged immigrant novel (i.e., by and about immigrants) in America” (Chametzky, 1971: 387). When the novel is looked from the historical perspective, it gives a great number of hints for understanding the terms of Jewish who lives in Russia before Pogroms and in America in 1920s. For example Marovitz depicts the novel as “a tale of industrial America” (205). However, some critics consider that the novel indicates a religious person’s failure in America. Barrish thinks that it “sets up just such a relation with what might be called the ethnic real in Levinsky's figuration of traditional Judaism as "fall[en] to pieces" in America” (656). No matter what is written for the novel, it encapsulates the life(style) and culture of the US. The author is also Lithuanian editor of the Jewish Daily Forward which is “the Lower East Side's most prominent Yiddish-language socialist newspaper” (Johnson, 90) and an activist who endeavors to shape American policy and enact the reforms about Jewish and newcomers. He is also interested in Russian Jews coming to America. Within this context, he is aware of his people, culture and the way of newcomers’ living and helps American politicians develop immigrant policy. His knowledge is reflected on the autobiographical novel. As a Jewish person who migrates to America, the author reverberates being other in a new land. Rottenberg claims that all incidences “suggest that Levinsky is interpellated into his new country as a foreigner and as a Jew” (318). His consciousness hails on the novel. Likewise, the author’s use of English is very important to broaden his voice. If the novel had been written in Yiddish language, the novel cannot have been so popular like that. Cahan’s popularity is due to writing in English language. As Sheffer states: “writing in English was a way to reach the literary mainstream and thereby achieve greater recognition, material comfort, and cultural legitimacy in the United States” (147). The usage of English makes the author more confident and embraced the US. In this regard, Cahan is very eager to adapt himself to the US and wants to be a member of its society. This autobiographic novel depicts the huge alteration in the protagonist’s mind. The novel starts with the sentence about reflecting Levinsky’s alteration: “when I think of my past in a superficial, casual way, the metamorphosis I have gone through strikes me as nothing short of a miracle” (Cahan, 3). Yet, this miracle also contains individual characteristics of a Jewish. Like his creator, Levinsky turns into a prototype which can be given an example to Jewish immigrants. The protagonist is likely to be reclaimed “in terms of the difficulties encountered in actually achieving success” (Miller, 15). In this context, the protagonist manages to represent the term and individuals of the then America. Because the novel has the feature of autobiography, it is more related to reality. In this sense, the novel can be argued in terms of historical, sociological and psychological perspective. The novel is prominent to understand better the US historically and sociologically. The critic asserts that all events and dialogues are: "historical" in a more modern sense because they deliberately show us how personality and culture interact in a particular style of life to pose issues in the life- cycle of developing individuals whose imaginary existence still has a local habitation and a name in actuality. (Strout, 437) Furthermore, these cultural and historical facts not only pictures the customs and culture of the societies Levinsky lives in but also indicates the problems or policies in Russian and American society. “As these novels indicate, ancestral narratives are more than family folklore because they are responses to fundamental problems in contemporary society, such as racism and assimilation”(Hein and Moore, 11). As the critics state, Russian racism and American assimilation are two major problems in the novel. Fleeing from the Gentiles who murder his mother, socialist Levinsky like his author lives under the shadow of capitalism. Levinsky turns into more American than an ordinary American. Moreover, his attempts to be a pious Jewish are in vain.Malinovich implying this novel and Nyburg'sThe Chosen People purports: “With their focus on the dilemmas posed by assimilation and acculturation, these novels reflect a rising skepticism about the melting pot ideal in American society” (32). The Rise of David Levinsky is a kind of novel containing historical, sociological and psychological background which depicts East European immigrants. Heinze depicts the protagonist as “psychologically traumatized Jewish immigrant” (978). However, the immigrants were highly influenced by him and his success. Continuing his protagonist’s depiction, Singer labels him as a “man who, more than any other individual, helped shape the cultural pattern of New York's Jewish community”(699) On the other hand; Levinsky succeeds in combination of history and fiction. Although this quotation is a bit long, it clearly summarizes the idea argued; The emergence of the communist states in East and Central Europe after World War II changed the political configurations across continents and affected cultures and literatures with the introduction of a new type of international artist-the dissident-who in turn changed the image of an East European immigrant in the United States from a lower-class laborer to a middle- or upper-class intellectual. The familiar rags-to-riches newcomer scenario has been replaced with a tale of political oppression, internal exile, and expulsion of radical writers, scientists, and artists who were often forced to immigrate because of their opposition against the regimes. (Zaborowska; 56)
A NEW HISTORICIST STUDY OF THE RISE OF DAVID LEVINSKY BY ABRAHAM CAHAN